Autoantibodies Against Lysosome Associated Membrane Protein-2 (LAMP-2) in Pediatric Chronic Primary Systemic Vasculitis - Gibson, Kristen M.; Kain, Renate; Luqmani, Raashid A.; Ross, Colin J.; Cabral, David A.; Brown, Kelly L. (Frontiers in Immunology, 2021)
Background Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a small vessel vasculitis in adults and children that commonly affects the kidneys. Although the frequent antigenic, and presumed pathogenic, targets of ANCA in AAV are proteinase-3 (PR3) and myeloperoxidase (MPO), ANCA against lysosome associated membrane protein-2 (LAMP-2), a lesser known ANCA antigen that is expressed on the glomerular endothelium, are present in some adults with AAV-associated renal disease. LAMP-2-ANCA has not been assessed in children with chronic systemic vasculitis, and, if present, would be a potentially valuable biomarker given that treatment decisions for these pediatric patients at diagnosis are largely informed by kidney function. Methods A custom ELISA, using commercially available reagents, was designed to detect autoantibodies to human LAMP-2 in serum. Sera obtained from 51 pediatric patients at the time of diagnosis of chronic primary systemic vasculitis (predominantly AAV) were screened. LAMP-2-ANCA titers were evaluated for correlation with clinical metrics of disease activity (pediatric vasculitis activity score [pVAS], C-reactive protein [CRP] concentration, and erythrocyte sedimentation rate [ESR]), MPO- and PR3-ANCA titers, and renal function (glomerular filtration rate [GFR], renal-specific pVAS, and serum creatinine concentration). Results LAMP-2-ANCA (>1,000 ng/ml) were detected in 35% (n = 18) of pediatric systemic vasculitis patients, of which, 10 (20% of all patients) were found to have high positive titers (>1,500 ng/ml). Undetectable or negative titres (<500 ng/ml) were identified in 12% (n = 6) of patients, those with titers between 500 and 1,000 ng/ml were considered low with unknown clinical relevance (53%, n = 27). Although LAMP-2-ANCA titers did not significantly differ between patients with AAV versus ANCA-negative vasculitis, only AAV patients had high concentrations (>1,500 ng/ml) of LAMP-2-ANCA. LAMP-2-ANCA titers did not correlate with measures of disease activity (pVAS, CRP, or ESR) at the time of diagnosis. In contrast, for patients with 12-month post diagnosis follow-up, a negative correlation was observed between the change in GFR (from diagnosis to 12-month follow-up) and LAMP-2-ANCA titer at diagnosis. Conclusions Moderate to high LAMP-2-ANCA titers were detected in 35% (18/51) of children with chronic systemic vasculitis affecting small-to-medium vessels. Although the highest concentrations of LAMP-2-ANCA in this population were observed in individuals positive for classic ANCA (MPO- or PR3-ANCA), similar to previous reports on adult patients, LAMP-2-ANCA titers do not correlate with classic ANCA titers or with overall disease activity at diagnosis. Renal disease is a common manifestation in systemic small-medium vessel vasculitis (both in adults and children, though more severe in children) and our preliminary data suggest LAMP-2-ANCA at diagnosis may be a risk factor for more severe renal disease.